PENGARUH BURSA SAHAM GLOBAL TERHADAP INDEKS HARGA SAHAM GABUNGAN DI BURSA EFEK INDONESIA: The Effect of Global Stock Exchanges on the Composite Stock Price Index on the Indonesia Stock Exchange - Lisa Kustina; Samsul Anwar; Imas Mawar (Jurnal Investasi, 2018)
Tujuan Penelitian ini adalah untuk mengetahui pengaruh bursa saham global terhadap indeks harga saham gabungan di Bursa Efek Indonesia. Bursa saham global yang digunakan dalam penelitian ini adalah Dow Jones Index (DJI), Korea Stock Price Composite Index (KOSPI), Tokyo Stock Exchange (Nikkei heikin kabuki / Nikkei 225), dan Australian Securities Exchange (ASX). Sampel yang diteliti dalam penelitian ini adalah periode 2015 hingga 2017. Penelitian ini menggunakan regresi linear berganda untuk mengolah data penelitian. Hasil Penelitian ini menunjukkan bahwa Dow Jones Index (DJI), Korea Stock Price Composite Index (KOSPI), Tokyo Stock Exchange (Nikkei heikin kabuki / Nikkei 225), dan Australian Securities Exchange (ASX) secara parsial berpengaruh terhadap Indek Harga Saham Gabungan diIndonesia. Dow Jones Index (DJI), Korea Stock Price Composite Index (KOSPI), dan Australian Securities Exchange (ASX) berpengaruh signifikan pada tingkat signifikansi 0.000 sedangkan Tokyo Stock Exchange (Nikkei 225) pada tingkat signifikansi 0.001. The purpose of this study was to determine the effect of global stock exchanges on the composite stock price index on the Indonesia Stock Exchange. The global stock exchanges used in this study are the Dow Jones Index (DJI), the Korea Stock Price Composite Index (KOSPI), the Tokyo Stock Exchange (Nikkei Heikin Kabuki / Nikkei 225), and the Australian Securities Exchange (ASX). The sample examined in this study is the period 2015 to 2017. This study uses multiple linear regression to process research data. The results of this study indicate that the Dow Jones Index (DJI), the Korea Stock Price Composite Index (KOSPI), the Tokyo Stock Exchange (Nikkei Heikin Kabuki / Nikkei 225), and the Australian Securities Exchange (ASX) partially affect the Composite Stock Price Index in Indonesia. The Dow Jones Index (DJI), the Korea Stock Price Composite Index (KOSPI), and the Australian Securities Exchange (ASX) have a significant effect on the significance level of 0,000 while the Tokyo Stock Exchange (Nikkei 225) is at a significance level of 0.001.